Goji Berry: a Novel Nutraceutical "Superfruit" for Florida Master Gardeners - Yujie Jiao; Guodong Liu (EDIS)
Goji berries have been used in both fresh and processed forms for food and medicine for more than 4,000 years in China. The goji berry fruit is known as a “superfruit” thanks to its high levels of vitamins and minerals, as well as other medicinal benefits recognized in many countries around the world. Most of Florida’s climate is favorable for goji berry, and a few Florida growers have cultivated it for years. This species can tolerate infertile and unfavorable growth conditions, and the prominent health benefits of this crop may be highly profitable for Florida growers. The objective of this new 7-page article is to provide a general overview of how the goji berry can be grown in Florida. Written by Yujie Jiao and Guodong Liu, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1391